Kompetensi Penyuluh Pertanian Lapangan dalam Kegiatan Penyuluhan Tanaman Jagung di Kabupaten Buton Utara - Batoa, Hartina; Wunawarsih, Ima Astuty; Hasnawati, Eka; Yusriadin, Yusriadin (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to determine the Competence of Agricultural Elucidator Workers through Maize Extension Activity at Labuan Village Wakorumba District of North Buton Regency. This research conducted in February 2014. Location of this research took place at Labuan village of North Wakorumba District North Buton Regency. The population of this study was the agricultural elucidator at Labuan village amount one person and 9 people of corn farmers that taken intentionally as the informants key with consideration attended counseling activities. Variables that watch in this study were: (1) The identity of the Agricultural Elucidator that consist of age, elucidator formal education experience, also the number of dependents. (2) The competence of Agricultural Elucidator technical that consist of the selection and the using of improved seed, fertilizer and pest control, and plant disease method; managerial competencies that consist of the timing of planting and fertilizing; communication competencies consist of delivery in extension activities and giving examples/demonstration method during extension activities. This research used qualitative descriptive analysis techniques. Technical competence of elucidator shows the knowledge of science that covers agricultural cultivation selection and the using of quality seeds, good fertilization, and control of pests and plant diseases. Selection and procurement of quality seeds and good fertilizers located in the middle category. Managerial competence of Elucidator in the timing of planting at the high category while the timing of fertilizer application in the middle category. Communication competence is the knowledge of employees to communicate well which use messages that considered appropriate and effective. The competence of Elucidator communication in delivering information and methods of a demonstration in the high category.